Technology-assisted reconstruction: a new alternative to the experience sampling method - Karapanos, Evangelos (My University, 2020)
Despite the recent increase in interest in the experience sampling method (ESM), researchers have repeatedly criticised the high burden and levels of interruption that it imposes on participants, and alternative cost-effective methods, such as the Day Reconstruction Method (DRM), have been adopted by the Human-Computer Interaction (HCI) community. In this paper, we review the use of ESM and DRM in the HCI field and argue for a new paradigm called Technology-Assisted Reconstruction (TAR), according to which passively logged data of users’ behaviours are used in assisting the later reconstruction of experiences and behaviours. We discuss five methods of Technology-Assisted Reconstruction that we have developed in our past work and conclude with a framework that highlights three directions for Technology-Assisted Reconstruction.
Keywords: Experience sampling; Day reconstruction; Ecological momentary assessment; Ambulatory assessment; Insitu measurement